Junie B. Jones and that meanie Jim's birthday - Park, Barbara (Park, Barbara. Junie B. Jones series, 1996)
Junie B is very upset when a boy in her class plans to invite everyone except her to his birthday party, but her grandfather helps her deal with the situation.